Constitutional Provisions In India And The Need For Gender Neutral Laws (Journal of Namibian Studies : History Politics Culture, 2023)
Gender neutrality within legal frameworks is a cornerstone of promoting fairness, equity, and justice for individuals of all genders. This paper critically examines the challenges, opportunities, and policy recommendations surrounding the implementation of gender-neutral laws in India, with a focus on addressing the misuse of laws by both men and women. Key areas of analysis include existing laws favoring women, such as those pertaining to domestic violence and sexual offenses, which often neglect the rights and protections of men. Conversely, laws neglecting men, such as those governing parental rights and child custody, perpetuate stereotypes and inequalities within society. Instances of law misuse further underscore the need for more balanced and equitable legal provisions, with recommendations including legislative reforms, institutional initiatives, and public awareness campaigns. Suggested policy recommendations emphasize the importance of enacting gender-neutral legislation, strengthening safeguards against law misuse, providing institutional training programs, launching public awareness campaigns, and investing in research and data collection efforts. By implementing these recommendations, policymakers can work towards creating a more just, equitable, and inclusive legal system that upholds the rights and dignity of all individuals, irrespective of their gender identity or expression.